Cardiovascular 24-h rhythms and renal excretory function in rats after allogeneic kidney transplantation - Witte, Klaus; Braun, Claude; Pummer, Stefan; Vetter, Stefan; Lemmer, Björn (Transplant international, 2003)
We investigated long-term and circadian blood-pressure changes in a Fischer → Lewis rat model of chronic renal allograft rejection. Ten days after allogeneic kidney transplantation, rats were equipped with telemetry transmitters for continuous monitoring of blood pressure. Urine was sampled 24, 96 and 180 days after kidney transplantation for measurement of renal protein loss and excretion of nitric oxide metabolities. Proteinuria increased with time after transplantation, while urinary excretion of nitric oxide metabolites declined. In five of six rats blood pressure remained in the normotensive range, and its 24-h pattern was preserved up to 6 months post-transplantation. One animal showed hypertensive blood pressure and a disturbed 24-h pattern with peak values during the rest period. In the post-mortem analysis this rat showed a hydronephrotic kidney graft. In conclusion, blood pressure and its 24-h pattern are preserved after successful allogeneic kidney transplantation in the rat.